Risk Factors for a False-Negative Examination in Complete Upper Extremity Nerve Lacerations. (July 2021) - Loewenstein, Scott N.; Wulbrecht, Reed; Leonhard, Vanessa; Sasor, Sarah; Cook, Julia; Timsina, Lava; Adkinson, Joshua
Background: Many patients with complete nerve lacerations after upper extremity trauma have a documented normal peripheral nerve examination at the time of initial evaluation. The purpose of this study was to determine whether physician-, patient-, and injury-related factors increase the risk of false-negative nerve examinations.Methods: A statewide health information exchange was used to identify complete upper extremity nerve lacerations subsequently confirmed by surgical exploration at 1 pediatric and 2 adult level I trauma centers in a single city from January 2013 to January 2017. Charts were manually reviewed to build a database that included Glasgow Coma Scale score, urine drug screen results, blood alcohol level, presence of concomitant trauma, type of injury, level of injury, laterality, initial provider examination, and initial specialist examination. Bivariate and multivariable analyses were performed to evaluate risk factors for a false-negative examination.Results: Two hundred eighty-eight patients met inclusion criteria. The overall false-negative examination rate was 32.5% at initial encounter, which was higher among emergency medicine physicians compared with extremity subspecialists ( P < .001) and among trauma surgeons compared with surgical subspecialists ( P = .002). The false-negative rate decreased to 8% at subsequent encounter ( P < .001). Risk factors for a false-negative nerve examination included physician specialty, a gunshot wound mechanism of injury, injury at the elbow, and age greater than 71 years.Conclusion: There is a high false-negative rate among upper extremity neurotmesis injuries. Patients with an injury pattern that may lead to nerve injury warrant prompt referral to an upper extremity specialist in an effort to optimize outcomes.